PENGUATAN KAPASITAS NELAYAN PERIKANAN SKALA KECIL TENTANG LOG BOOK DAN KONSERVASI - Waileruny, Welem; Matrutty, Delly DP; Uneputty, Prulley A (Balobe: Jurnal Pengabdian Masyarakat, 2024)
Small-scale fisheries play a vital role in the economy and food security of both local and national communities. However, in carrying out their activities, they face various obstacles, including the weakness of human resource capabilities and the challenge of declining fishery resources. Therefore, efforts to improve the capacity of small-scale fishers are essential. This community service activity (PkM) aims to enhance the capacity of small-scale fishers in fish catch logbooks and fishery resource conservation to ensure business sustainability. This PkM was conducted by presenting material by resource persons, followed by discussions and question-and-answer sessions. The participants of this activity came from Tulehu, Waai, and Liang Villages in Salahutu District, Central Maluku Regency, which was held in Negeri Waai. For the fishers, the implementation of this PkM is very beneficial because they can gain knowledge and skills in using logbooks that have not been done so far. The completion of logbooks, which has become an obligation for fishers both nationally and internationally, is still unknown and not practiced by many fishers. After participating in this PkM, they understand the importance of filling out logbooks. In terms of conservation, fishers are already aware of fishery resource conservation by using environmentally friendly fishing gear. However, they still need assistance and capacity-building as fishers.